2006
DOI: 10.1159/000097466
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sedation for Routine Diagnostic Upper Gastrointestinal Endoscopy: A European Society of Gastrointestinal Endoscopy Survey of National Endoscopy Society Members

Abstract: Background/Aims: Sedation rates may vary among countries, depending on patients’ and endoscopists’ preferences. The aim of this survey was to investigate the rate of using premedication for routine diagnostic upper gastrointestinal (UGI) endoscopy in endoscopy societies, members of the European Society of Gastrointestinal Endoscopy (ESGE). Methods: We evaluated a multiple-choice questionnaire which was e-mailed to representatives of national endoscopy societies, which are members of the ESGE. The questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 32 publications
0
43
0
3
Order By: Relevance
“…In the UK, the sedation rate decreased by 54%, from 70% in 1990 to 32% in 1998 [7], while in Switzerland it increased, with 77% of the endoscopists sedating their patients in 2003 [8]. The results of a recent European survey (29 countries) showed that in about 50% of the countries, less than 25% of the patients undergo routine diagnostic upper GI endoscopy with sedation [9] (fig. 1).…”
Section: Upper Gi Endoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…In the UK, the sedation rate decreased by 54%, from 70% in 1990 to 32% in 1998 [7], while in Switzerland it increased, with 77% of the endoscopists sedating their patients in 2003 [8]. The results of a recent European survey (29 countries) showed that in about 50% of the countries, less than 25% of the patients undergo routine diagnostic upper GI endoscopy with sedation [9] (fig. 1).…”
Section: Upper Gi Endoscopymentioning
confidence: 99%
“…These included diazepam, midazolam, meperidine, fentanyl and propofol, with the most popular being midazolam and propofol [9]. It is important to note that in 8 of 12 countries where an anesthesiologist sedated the patients and propofol was included in the list of the preferred sedatives, the sedation rate was less than 25% [9]. …”
Section: Upper Gi Endoscopymentioning
confidence: 99%
“…However, survey respondents were distributed relatively evenly between different endoscopy practices, and an international audit with a larger panel of individual respondents than reported here is notably difficult to organize [27,28] .…”
Section: Discussionmentioning
confidence: 92%
“…3 Similarly, there is concordance between the responses of European endoscopists in this survey and the results of two recent European studies on sedation practices. 5,14 In summary, our results suggest that (1) a web-based survey can efficiently yield data regarding endoscopic practices on a world-wide scale, including from developing countries; (2) during the past 5 years, the use of sedation for endoscopy has increased in many countries, with unsedated procedures being the majority method in only a small proportion of countries represented in this survey; (3) a benzodiazepine/opioid combination remains the most common majority practice, although propofol use is rapidly gaining popularity; and (4) most practitioners represented in this survey adhere to published guidelines regarding intra-procedural monitoring. A global web-based survey of a larger number of practitioners (perhaps utilizing a database from a global endoscopy society) could further substantiate our findings.…”
Section: Discussionmentioning
confidence: 99%